Hubungan Tingkat Stres Akademik dan Kecenderungan Sindrom Makan Malam dengan Status Gizi pada Remaja - Tetasa, Sarah; Muniroh, Lailatul; Puspita, Fina Intan (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze the relationship between academic stress levels and the tendency for night eating syndrome to occur with nutritional status in adolescents. This research used an observational method with a cross sectional approach, then a proportional random sampling technique was used to obtain a minimum sample size of 81 people. Anthropometric measurements, interviews and filling out several questionnaires such as the Educational Stress Scale for Adolescents (ESSA), and the Night Eating Questionnaire (NEQ), were carried out to obtain data which was then processed using the Spearman Rank Correlation Test. The results showed that the level of academic stress and the tendency for night eating syndrome were related to nutritional status in adolescents. The higher the level of academic stress and the tendency for night eating syndrome, the greater the possibility that teenagers will have poor nutritional status. This is due to the consumption of foods high in fat and sugar after dinner, so teenagers are advised to control food intake and limit consumption of foods high in fat and sugar.